A dual phosphorus source gradient layered catalyst and its application in ethanethiol synthesis
By employing a dual-phosphorus-source gradient layered structure in the ethanethiol synthesis catalyst, the inner layer constructs a dual synergistic active system of metal single atoms and transition metal phosphide clusters, while the outer layer forms an anti-carbon deposition protection system of phosphorus pentoxide and multi-component oxides. This solves the problem of balancing catalyst activity, selectivity, and stability, and achieves highly efficient ethanethiol synthesis.
Patent Information
- Application Number
- CN202611206223.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-11-06
AI Technical Summary
Existing catalysts for the synthesis of ethanethiol suffer from difficulties in achieving a balance between catalytic activity, selectivity, and stability. They also exhibit poor resistance to carbon deposition at high temperatures, low product desorption efficiency, and insufficient synergistic effect of active components, which limits their industrial application and efficient production.
It adopts a dual phosphorus source gradient layered structure. The inner layer consists of a dual synergistic active system composed of metal single atoms and transition metal phosphide clusters, while the outer layer consists of a dual protective system composed of phosphorus pentoxide and multi-element oxide additives. The regular structure is formed by gradient step-by-step impregnation and segmented calcination process to avoid component mixing and functional interference.
It significantly improves the activity, selectivity and stability of the catalyst, inhibits the formation of byproducts, and extends the catalyst's lifespan, making it suitable for large-scale industrial production.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst technology, specifically relating to a highly stable ethanethiol synthesis catalyst with dual phosphorus source gradient stratification and its preparation method. Background Technology
[0002] Ethyl mercaptan is an important organosulfur fine chemical raw material, widely used in pesticides, pharmaceuticals, rubber additives, petroleum additives, and other fields. The mainstream industrial preparation process involves the catalytic addition sulfidation reaction of ethylene with hydrogen sulfide. This process has the advantages of readily available raw materials and a short reaction route, but it relies heavily on the catalytic action of a high-performance catalyst. The activity, selectivity, and stability of the catalyst directly determine the yield and production cost of ethyl mercaptan.
[0003] Currently, most industrially used catalysts for ethanethiol synthesis are single-transition-metal supported alumina catalysts, which have several technical drawbacks: First, the active component is of a single form, with a limited number of catalytic sites, resulting in insufficient ethylene activation and hydrogen sulfide adsorption activation capabilities, leading to low ethylene conversion and ethanethiol selectivity, and high content of byproducts such as sulfides and disulfides, resulting in high product purification costs. Second, under medium- and high-temperature reaction conditions, the active metal component is prone to agglomeration and sintering, causing rapid decay of catalytic activity. Third, ethylene is an unsaturated olefin, which is prone to polymerization and dehydrogenation reactions on the catalyst surface, causing severe carbon deposition and coking, clogging catalyst channels and covering active sites, resulting in a significant reduction in catalyst lifespan. Industrial plants need to frequently shut down to replace the catalyst, seriously affecting continuous production efficiency. Fourth, traditional preparation processes often use co-impregnation methods, resulting in disordered distribution of active components and anti-coking agents. The agents easily coat the active sites, further reducing catalytic efficiency, and the uneven distribution of components leads to poor batch stability of the catalyst, making it difficult to achieve stable large-scale industrial production.
[0004] While some existing technologies have improved the anti-coking properties of catalysts through doping with additives, these methods generally suffer from limitations in achieving a single modification effect and failing to simultaneously achieve high activity, high selectivity, and long-term stability. They fail to address the core bottlenecks through the synergistic design of catalyst structure, active system, and anti-coking system, significantly hindering the industrial-scale promotion and efficient production of ethanethiol via ethylene sulfidation. Therefore, developing an ethanethiol synthesis catalyst that combines high catalytic activity, high product selectivity, strong anti-coking ability, and long service life is a pressing technical problem that needs to be solved in this field. Summary of the Invention
[0005] Addressing the core technical challenges of the prior art, such as the difficulty in simultaneously achieving catalytic activity, selectivity, and stability, poor resistance to carbon deposition at high temperatures, low product desorption efficiency, and insufficient synergistic effect of active components, this invention provides a dual-phosphorus-source gradient-layered high-stability ethanethiol synthesis catalyst and its preparation method. Using shaped alumina as a carrier, it features a unique gradient-layered, well-organized structure with an internal active layer and an external protective layer. The entire process employs independent, step-by-step loading of two phosphorus sources, completely differentiating it from the existing single-phosphorus-source blending modification model. This invention strictly separates the phosphorus source into an active phosphorus source and a protective phosphorus source, with the two types of phosphorus sources introduced step-by-step, layered, functionally independent, and without interference.
[0006] The inner active region consists of a dual synergistic active system composed of metal single atoms and transition metal phosphide clusters. The metal single atoms provide highly selective addition sites, precisely constraining the ethylene addition reaction pathway and inhibiting the formation of byproducts such as sulfides and disulfides. The transition metal phosphide clusters are generated in situ from the active phosphorus source, which can significantly enhance the adsorption and activation capacity of hydrogen sulfide and improve the conversion efficiency of the main reaction. The two work together to achieve a highly active and highly selective catalytic effect.
[0007] The outer protective area consists of a dual-effect protection system composed of an inner transitional anti-carbon deposition layer and an outer surface anti-carbon deposition functional layer. It uses phosphorus pentoxide as a dedicated protective phosphorus source, combined with multi-element oxide additives, which are only used to regulate the acid-base properties of the catalyst surface, inhibit olefin polymerization and coking, and block the high-temperature agglomeration and sintering of active metals. It does not participate in or interfere with the construction of the inner active site, thus solving the core contradiction of traditional phosphorus-modified passivation activity from the root.
[0008] The molded alumina carrier is γ-Al₂O₃ with a specific surface area of 180-280 m². 2 / g, pore volume 0.4-0.8 cm³ 3 / g, the carrier morphology is one of spherical, strip-shaped, or toothed spherical.
[0009] The active component in the first active layer is a metal single atom. The metal precursor is one or more metal salt aqueous solutions selected from Ni(NO3)2, Mn(NO3)2, Zr(NO3)4, Fe(NO3)3, AgNO3, Pt(NO3)2, Pd(NO3)2, and Au(NO3)2. The metal precursor is loaded by an equal volume impregnation method, and the loading amount is 0.1-4 wt%, preferably 0.2-2 wt%.
[0010] The active component in the second active layer is a transition metal phosphide cluster, which is one or more of CoP, MoP, CuP2, Ni2P, WP, and VP.
[0011] The active phosphorus source is one or two of phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate, and ammonium hypophosphite, with a loading of 0.1-2 wt% (calculated as P).
[0012] The third transitional anti-carbon deposition layer is composed of phosphorus pentoxide and an anti-carbon deposition additive, wherein the first anti-carbon deposition additive and the second anti-carbon deposition additive are one or more of silicon dioxide, titanium dioxide, and zinc oxide.
[0013] Based on the total mass of the catalyst, the total loading of the metal dual synergistic active system is 1-8 wt%, the loading of the protective phosphorus source phosphorus pentoxide is 2-10 wt%, and the total loading of the anti-carbon deposition additive is 1-3 wt%.
[0014] This invention employs an optimized gradient step-by-step impregnation and segmented calcination process, in which each functional layer is formed and cured sequentially, avoiding problems such as component mixing, site encapsulation, and functional interference. The catalyst has a regular structure, stable performance, and good batch consistency, making it suitable for large-scale industrial production.
[0015] To achieve the above objectives, the present invention adopts the following technical solution: Step 1: Carrier pretreatment: Place the shaped alumina carrier at 400-500℃ for 2-4 hours, and cool it to room temperature for later use; Step 2: Gradient construction of dual synergistic active layers: A stepwise impregnation process is adopted. First, a metal single-atom precursor solution A is prepared, and the carrier is impregnated for 2-4 hours. After aging for 1-2 hours, drying at 100-120℃ for 4-6 hours, and calcining at 400-480℃ for 2-3 hours, the first active layer is formed. Then, a mixed solution B containing an active phosphorus source and a transition metal precursor is prepared, impregnated, and calcined in stages to generate transition metal phosphide clusters in situ, forming the second active layer. Step 3: Constructing the inner transitional anti-carbon deposition layer: Prepare an impregnation solution C containing phosphorus pentoxide and the first anti-carbon deposition additive, and perform secondary modification on the carrier loaded with the double active layer. After impregnation for 1-3 h, aging for 0.5-1 h, drying at 110-130℃ for 3-5 h, and calcination at 380-450℃ for 1.5-2.5 h, the third transitional anti-carbon deposition layer is obtained. Step 4: Construct the outer anti-carbon deposition functional layer: Prepare a composite impregnation solution D containing phosphorus pentoxide and a second anti-carbon deposition additive, load it onto the outermost layer using a surface gradient impregnation method, and obtain the final gradient layered catalyst after aging, drying and final calcination.
[0016] Furthermore, the impregnation, drying, and calcination processes of the transition metal phosphide precursor are consistent with those of the single-atom active layer; the impregnation, drying, and calcination processes in the preparation of the outer anti-carbon deposition functional layer are consistent with those in the preparation of the inner transition anti-carbon deposition layer.
[0017] Furthermore, in step 2, the transition metal is Co(NO3)2, Cu(NO3)2, Ni(NO3)2, or (NH4)6Mo7O. 24 H 28 N6O41 W 12 One or more of NH4VO3, with a loading of 1-10 wt%, preferably 1-6 wt%.
[0018] Furthermore, in step 2, the active phosphorus source is one or two of phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate, and ammonium hypophosphite, with a loading of 0.1-2 wt% (based on P), preferably 0.2-1.0 wt%.
[0019] Furthermore, the precursors of the first and second anti-carbon deposit additives in steps 3 and 4 are one or more of silica sol, tetraethyl orthosilicate, titanium sol, tetrabutyl titanate, and zinc nitrate, and the loading of the additives is 2-6 wt% (based on oxides), preferably 1-4 wt%.
[0020] The third transitional anti-carbon deposition layer is composed of phosphorus pentoxide and an anti-carbon deposition additive, wherein the first anti-carbon deposition additive and the second anti-carbon deposition additive are one or more of silicon dioxide, titanium dioxide, and zinc oxide.
[0021] In step 2, the single-atom precursor is impregnated for 2-4 hours, aged for 1-2 hours, dried at 100-120℃ for 4-6 hours, and calcined at 400-480℃ for 2-3 hours; the impregnation, drying, and calcination processes of the transition metal phosphide precursor are consistent with those of the single-atom active layer. In steps 3 and 4, the impregnation time is 1-3 hours, the aging time is 0.5-1 hour, the drying temperature is 110-130℃, the drying time is 3-5 hours, the calcination temperature is 380-450℃, and the calcination time is 1.5-2.5 hours.
[0022] A dual-phosphorus source gradient stratified catalyst, prepared by the method described above, wherein the total loading of the metal dual synergistic active system is 1-8 wt% by total catalyst mass, the loading of the protective phosphorus source phosphorus pentoxide is 2-10 wt%, and the total loading of the anti-carbon deposition agent is 1-3 wt%.
[0023] Another technical solution of the present invention is the application of the aforementioned dual-phosphorus source gradient stratified catalyst in the catalytic synthesis of ethanethiol.
[0024] The catalyst is used in the catalytic reaction of ethylene sulfidation to prepare ethanethiol, under the conditions of 180-210℃, 1.1-1.6 MPa, an ethylene to hydrogen sulfide molar ratio of 1:1.05-1.2, and a volume hourly space velocity of 800-1200 h⁻¹. -1 Ethylene conversion rate ≥98%, ethanethiol selectivity ≥96%.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention adopts a unique gradient layered regular structure of "active layer built-in, protective layer external" to form γ Using Al2O3 as a carrier, the dual phosphorus sources are strictly separated into an active phosphorus source and a protective phosphorus source, which are then independently loaded. In the inner layer, a dual-synergistic active system composed of metal single atoms and transition metal phosphide clusters is constructed sequentially; in the outer layer, a dual-effect anti-carbon deposition protective system composed of phosphorus pentoxide and multi-element oxide additives is formed. Combining gradient stepwise impregnation and segmented calcination processes, each functional layer is solidified layer by layer without interference. This bilayer phosphorus-based protective structure effectively inhibits olefin polymerization carbon deposition and the agglomeration and sintering of active metals at high temperatures, while significantly reducing the formation of byproducts such as sulfides and disulfides. The catalyst maintains high efficiency and no significant degradation even after more than 1000 hours of continuous operation, demonstrating broad prospects for industrial applications. Detailed Implementation
[0026] The present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments.
[0027] Example 1: NiSA-CoP / Si-Ti A method for preparing a dual-phosphorus-source gradient-stratified, highly stable, and anti-carbon-depositing ethanethiol synthesis catalyst includes the following steps: Step 1: Support pretreatment: Select 100g of spherical γ-Al2O3 support with a specific surface area of 220 m². 2 / g, pore volume 0.6cm 3 / g, placed in a muffle furnace at 500℃ for 4 hours, naturally cooled to room temperature, and sealed for later use; Step 2: Gradient loading of dual active layers: 2.48g of nickel nitrate hexahydrate was dissolved in water to form the first active impregnation solution A. 100g of alumina balls treated in Step 1 were added to the first active impregnation solution A using an equal-volume impregnation method. The mixture was impregnated at room temperature for 3 hours, allowed to stand for 1.5 hours, dried at 110℃ for 5 hours, and calcined at 450℃ for 2.5 hours to prepare catalyst A. Then, 9.88g of cobalt nitrate hexahydrate and 1.86g of ammonium dihydrogen phosphate were dispersed in water to form a clear and transparent mixed solution B. The obtained catalyst A was added to the mixed solution B, and the same impregnation, aging, drying, and calcination process was used to generate the second active layer of CoP phosphide clusters in situ, thus obtaining catalyst B. Step 3: Preparation of inner transition anti-carbon deposition layer: 2g of phosphorus pentoxide and 3.33g of 30% silica sol were dispersed in water to form composite impregnation solution C. The solution was impregnated for 2h, aged for 1h, dried at 120℃ for 4h, and calcined at 420℃ for 2h to obtain catalyst C. Step 4: Preparation of outer anti-carbon deposition functional layer: Prepare impregnation solution D containing 2g phosphorus pentoxide and 5g 20% titanium sol, impregnate the surface for 1.5h, age for 0.5h, dry at 120℃ for 4h, and finally calcine at 400℃ for 2h to obtain the dual phosphorus source gradient stratified catalyst.
[0028] Performance testing: reaction temperature 195℃, pressure 1.3 MPa, ethylene to hydrogen sulfide molar ratio 1:1.1, volume hourly space velocity 1000 h⁻¹ -1 Test results: Ethylene conversion rate 99.1%, ethanethiol selectivity 97.8%.
[0029] Example 2: ZrSA-VP / Zn-Si A method for preparing a dual-phosphorus-source gradient-stratified, highly stable, and anti-carbon-depositing ethanethiol synthesis catalyst includes the following steps: Step 1: Support pretreatment: Select 100g of spherical γ-Al2O3 support with a specific surface area of 220 m². 2 / g, pore volume 0.6cm 3 / g, placed in a muffle furnace at 500℃ for 4 hours, naturally cooled to room temperature, and sealed for later use; Step 2: Gradient loading of dual active layers: 2.35g of zirconium nitrate pentahydrate was dissolved in water to form the first active impregnation solution A. 100g of alumina balls treated in Step 1 were added to the first active impregnation solution A using an equal-volume impregnation method. The mixture was impregnated at room temperature for 3 hours, allowed to stand for 1.5 hours, dried at 110℃ for 5 hours, and calcined at 450℃ for 2.5 hours to prepare catalyst A. 0.61g of ammonium metavanadate and 1.86g of ammonium dihydrogen phosphate were then dispersed in water to form a clear and transparent mixed solution B. The obtained catalyst A was added to the mixed solution B, and the same impregnation, aging, drying, and calcination processes were performed to generate the second active layer of VP phosphide clusters in situ, thus obtaining catalyst B. Step 3: Preparation of the inner transition anti-carbon deposition layer: 2g of phosphorus pentoxide and 4.54g of zinc nitrate hexahydrate are dispersed in water to form a composite impregnation solution C. The solution is impregnated for 2 hours, aged for 1 hour, dried at 120℃ for 4 hours, and calcined at 420℃ for 2 hours to obtain catalyst C. Step 4: Preparation of outer anti-carbon deposition functional layer: Prepare impregnation solution D containing 2g phosphorus pentoxide and 3.33g 20% silica sol, impregnate the surface for 1.5h, age for 0.5h, dry at 120℃ for 4h, and finally calcine at 400℃ for 2h to obtain the dual phosphorus source gradient stratified catalyst.
[0030] Performance testing: reaction temperature 185℃, pressure 1.2 MPa, ethylene to hydrogen sulfide molar ratio 1:1.08, volume hourly space velocity 900 h⁻¹ -1 Test results: Ethylene conversion rate 98.2%, ethanethiol selectivity 96.7%.
[0031] Example 3: NiSA-MoP / Ti-Zn A method for preparing a dual-phosphorus-source gradient-stratified, highly stable, and anti-carbon-depositing ethanethiol synthesis catalyst includes the following steps: Step 1: Support pretreatment: Select 100g of spherical γ-Al2O3 support with a specific surface area of 220 m². 2 / g, pore volume 0.6cm 3 / g, placed in a muffle furnace at 500℃ for 4 hours, naturally cooled to room temperature, and sealed for later use; Step 2: Gradient loading of dual active layers: 2.48g of nickel nitrate hexahydrate was dissolved in water to form the first active impregnation solution A. 100g of alumina balls treated in Step 1 were added to the first active impregnation solution A using an equal-volume impregnation method. The mixture was impregnated at room temperature for 3 hours, allowed to stand for 1.5 hours, dried at 110℃ for 5 hours, and calcined at 450℃ for 2.5 hours to prepare catalyst A. 0.92g of ammonium heptamolybdate tetrahydrate and 1.86g of ammonium dihydrogen phosphate were then dispersed in water to form a clear and transparent mixed solution B. The obtained catalyst A was added to the mixed solution B, and the same impregnation, aging, drying, and calcination processes were performed to generate the second active layer of MoP phosphide clusters in situ, thus obtaining catalyst B. Step 3: Preparation of inner transition anti-carbon deposition layer: 2g of phosphorus pentoxide and 5g of 30% titanium sol are dispersed in water to form composite impregnation solution C. Impregnate for 2h, age for 1h, dry at 120℃ for 4h, and calcine at 420℃ for 2h to obtain catalyst C; Step 4: Preparation of the outer anti-carbon deposition functional layer: Prepare impregnation solution D containing 2g of phosphorus pentoxide and 4.54g of zinc nitrate hexahydrate, impregnate the surface for 1.5h, age for 0.5h, dry at 120℃ for 4h, and finally calcine at 400℃ for 2h to obtain the dual phosphorus source gradient stratified catalyst.
[0032] Performance testing: reaction temperature 190℃, pressure 1.3 MPa, ethylene to hydrogen sulfide molar ratio 1:1.1, volume hourly space velocity 1000 h⁻¹ -1 Test results: Ethylene conversion rate 98.9%, ethanethiol selectivity 97.5%.
[0033] Example 4: AgSA-CoP / Si-Ti A method for preparing a dual-phosphorus-source gradient-stratified, highly stable, and anti-carbon-depositing ethanethiol synthesis catalyst includes the following steps: Step 1: Support pretreatment: Select 100g of spherical γ-Al2O3 support with a specific surface area of 220 m². 2 / g, pore volume 0.6cm 3 / g, placed in a muffle furnace at 500℃ for 4 hours, naturally cooled to room temperature, and sealed for later use; Step 2: Gradient loading of dual active layers: 0.78g of silver nitrate was dissolved in water to form the first active impregnation solution A. 100g of alumina balls treated in Step 1 were added to the first active impregnation solution A using an equal-volume impregnation method. The mixture was impregnated at room temperature for 3 hours, allowed to stand for 1.5 hours, dried at 110℃ for 5 hours, and calcined at 450℃ for 2.5 hours to prepare catalyst A. 9.88g of cobalt nitrate hexahydrate and 1.58g of phosphoric acid were then dispersed in water to form a clear and transparent mixed solution B. The obtained catalyst A was added to the mixed solution B, and the same impregnation, aging, drying, and calcination processes were performed to generate the second active layer of CoP phosphide clusters in situ, thus obtaining catalyst B. Step 3: Preparation of inner transition anti-carbon deposition layer: 2g of phosphorus pentoxide and 3.33g of 30% silica sol were dispersed in water to form composite impregnation solution C. The solution was impregnated for 2h, aged for 1h, dried at 120℃ for 4h, and calcined at 420℃ for 2h to obtain catalyst C. Step 4: Preparation of outer anti-carbon deposition functional layer: Prepare impregnation solution D containing 2g phosphorus pentoxide and 5g 20% titanium sol, impregnate the surface for 1.5h, age for 0.5h, dry at 120℃ for 4h, and finally calcine at 400℃ for 2h to obtain the dual phosphorus source gradient stratified catalyst.
[0034] Performance testing: reaction temperature 190℃, pressure 1.25 MPa, ethylene to hydrogen sulfide molar ratio 1:1.09, volume hourly space velocity 950 h⁻¹ -1 Test results: Ethylene conversion rate 98.1%, ethanethiol selectivity 96.4%.
[0035] Example 5: FeSA-Ni2P / Si-Ti A method for preparing a dual-phosphorus-source gradient-stratified, highly stable, and anti-carbon-depositing ethanethiol synthesis catalyst includes the following steps: Step 1: Support pretreatment: Select 100g of spherical γ-Al2O3 support with a specific surface area of 220 m². 2 / g, pore volume 0.6cm 3 / g, placed in a muffle furnace at 500℃ for 4 hours, naturally cooled to room temperature, and sealed for later use; Step 2: Gradient loading of dual active layers: 3.45g of ferric nitrate nonahydrate was dissolved in water to form the first active impregnation solution A. 100g of alumina balls treated in Step 1 were added to the first active impregnation solution A using the equal-volume impregnation method. The mixture was impregnated at room temperature for 3 hours, allowed to stand for 1.5 hours, dried at 110℃ for 5 hours, and calcined at 450℃ for 2.5 hours to prepare catalyst A. Then, 9.64g of nickel nitrate hexahydrate and 1.34g of ammonium hypophosphate were dispersed in water to form a clear and transparent mixed solution B. The obtained catalyst A was added to the mixed solution B, and the same impregnation, aging, drying, and calcination process was performed to generate the second active layer of Ni2P phosphide clusters in situ, thus obtaining catalyst B. Step 3: Preparation of inner transition anti-carbon deposition layer: 2g of phosphorus pentoxide and 3.33g of 30% silica sol were dispersed in water to form composite impregnation solution C. The solution was impregnated for 2h, aged for 1h, dried at 120℃ for 4h, and calcined at 420℃ for 2h to obtain catalyst C. Step 4: Preparation of outer anti-carbon deposition functional layer: Prepare impregnation solution D containing 2g phosphorus pentoxide and 5g 20% titanium sol, impregnate the surface for 1.5h, age for 0.5h, dry at 120℃ for 4h, and finally calcine at 400℃ for 2h to obtain the dual phosphorus source gradient stratified catalyst.
[0036] Performance testing: reaction temperature 195℃, pressure 1.3 MPa, ethylene to hydrogen sulfide molar ratio 1:1.1, volume hourly space velocity 1000 h⁻¹ - ¹. Test results: Ethylene conversion rate 98.7%, ethanethiol selectivity 96.7%.
[0037] Example 6: MnSA-CuP2 / Si-Ti A method for preparing a dual-phosphorus-source gradient-stratified, highly stable, and anti-carbon-depositing ethanethiol synthesis catalyst includes the following steps: Step 1: Support pretreatment: Select 100g of spherical γ-Al2O3 support with a specific surface area of 220 m². 2 / g, pore volume 0.6cm 3 / g, placed in a muffle furnace at 500℃ for 4 hours, naturally cooled to room temperature, and sealed for later use; Step 2: Gradient loading of dual active layers: 2.14g of manganese nitrate tetrahydrate was dissolved in water to form the first active impregnation solution A. 100g of alumina balls treated in Step 1 were added to the first active impregnation solution A using the equal-volume impregnation method. The mixture was impregnated at room temperature for 3 hours, allowed to stand for 1.5 hours, dried at 110℃ for 5 hours, and calcined at 450℃ for 2.5 hours to prepare catalyst A. 8.01g of copper nitrate hexahydrate and 1.86g of ammonium dihydrogen phosphate were then dispersed in water to form a clear and transparent mixed solution B. The obtained catalyst A was added to the mixed solution B, and the same impregnation, aging, drying, and calcination processes were performed to generate the second active layer of CuP2 phosphide clusters in situ, thus obtaining catalyst B. Step 3: Preparation of inner transition anti-carbon deposition layer: 2g of phosphorus pentoxide and 3.33g of 30% silica sol were dispersed in water to form composite impregnation solution C. The solution was impregnated for 2h, aged for 1h, dried at 120℃ for 4h, and calcined at 420℃ for 2h to obtain catalyst C. Step 4: Preparation of outer anti-carbon deposition functional layer: Prepare impregnation solution D containing 2g phosphorus pentoxide and 5g 20% titanium sol, impregnate the surface for 1.5h, age for 0.5h, dry at 120℃ for 4h, and calcine at 400℃ for 2h to finally obtain the dual phosphorus source gradient stratified catalyst.
[0038] Performance testing: reaction temperature 195℃, pressure 1.3 MPa, ethylene to hydrogen sulfide molar ratio 1:1.1, volume hourly space velocity 1000 h⁻¹ -1 Test results: Ethylene conversion rate 98.3%, ethanethiol selectivity 96.2%.
[0039] Comparative Example 1: Blended catalyst CK-1 An impregnation solution was prepared by mixing equal amounts of the metal precursor, phosphorus source, and anti-carbon deposition agent as in Example 1. 100g of alumina balls pretreated in step 1 of Example 1 were added to the impregnation solution using the equal volume impregnation method. The catalyst CK-1 was obtained by calcination at 420℃ for 4h.
[0040] Performance testing: Under the same test conditions as in Example 1, the ethylene conversion rate was 62.5% and the ethanethiol selectivity was 88.1%.
[0041] Comparative Example 2: Gradient catalyst CK-2 without bilayer P2O5 protection Phosphorus pentoxide was removed from steps 3 and 4 of Example 1, while the other steps were the same as in Example 1, to obtain the CK-2 catalyst.
[0042] Performance testing: Under the same test conditions as in Example 1, the ethylene conversion rate was 97.2% and the ethanethiol selectivity was 73.5%.
[0043] Comparative Example 3: Single Phosphorus Source Gradient Modified Catalyst CK-3 The ammonium dihydrogen phosphate in step 2 of Example 1 was replaced with phosphorus pentoxide, and the other steps were the same as in Example 1, to obtain the CK-3 catalyst.
[0044] Performance testing: Under the same test conditions as in Example 1, the ethylene conversion rate was 84.6% and the ethanethiol selectivity was 91.2%.
[0045] Comparative Example 4: CK-4 system with a single active CoP site Step 1: Support pretreatment: Select 100g of spherical γ-Al2O3 support with a specific surface area of 220 m². 2 / g, pore volume 0.6cm 3 / g, placed in a muffle furnace at 500℃ for 4 hours, naturally cooled to room temperature, and sealed for later use; Step 2: Single active layer loading: 9.88g of cobalt nitrate hexahydrate and 1.86g of ammonium dihydrogen phosphate are dispersed in water to form a clear and transparent mixed solution B. 100g of pretreated spherical γ-Al2O3 support is added to mixed solution B, and impregnation, aging, drying and calcination are carried out in situ to generate the second active layer of CoP phosphide clusters, thus obtaining catalyst B. Steps 3 and 4 are the same as in Example 1, and the CK-4 catalyst is obtained.
[0046] Performance testing: Under the same test conditions as in Example 1, the ethylene conversion rate was 75.1%, the ethanethiol selectivity was 82.3%, and the contents of byproducts sulfides and disulfides were significantly increased. This demonstrates that the single-atom-phosphide cluster dual-cooperative structure can precisely constrain the main reaction pathway and suppress side reactions, which is the core guarantee for high selectivity.
[0047] Comparative Example 5: CK-5, a modified system without double-layer additives for protection The first anti-coking agent SiO2 and the second anti-coking agent TiO2 in steps 3 and 4 of Example 1 were removed, and the other steps were the same as in Example 1, to obtain catalyst CK-5.
[0048] Performance testing: Under the same test conditions as in Example 1, the short-term ethylene conversion rate reached 97.0%, but the long-term stability declined significantly. After 600 hours of operation, the performance degraded by more than 12%, with obvious metal sintering and severe pore blockage. This demonstrates that the synergistic protection of the SiO2 / TiO2 bilayer additive is a necessary condition for achieving ultra-long-term stable operation of 1000 hours.
[0049] Application Example 1: The catalysts from the examples and comparative examples were respectively loaded into industrial-grade fixed-bed reactors, and the reaction was carried out at a hydrogen sulfide / ethylene feed molar ratio of 1.1, a temperature of 195°C, a pressure of 1.3 MPa, and a reaction space velocity of 1000 h⁻¹. -1 Stability tests were conducted under the reaction conditions. The NiSA-CoP / Si-Ti catalysts in Examples 1-6 maintained ≥98% ethylene conversion and ≥96% ethanethiol yield after 1000 h of operation, demonstrating excellent stability.
[0050] Table 1. Comparison of the ethanethiol synthesis performance of a series of alumina-supported catalysts
[0051] This invention relates to a dual-phosphorus source gradient-layered high-stability ethanethiol synthesis catalyst. It employs a gradient-layered loading structure, with a first active layer, a second active layer, a third anti-coking layer, and an outer anti-coking functional layer sequentially arranged on the support from the inside out, overcoming the structural defects of traditional blended loading. The inner double-layered active layer ensures the core catalytic performance of the catalyst, providing sufficient active sites for the reaction. The middle third anti-coking layer can prevent the high-temperature agglomeration and sintering of active components, while simultaneously constructing a dual-effect anti-coking system with the active metal component, inhibiting olefin polymerization coking from the source. The outer anti-coking functional layer can isolate large molecular impurities in the reaction system, further enhancing anti-coking ability and protecting internal active sites. The anti-coking layer uses phosphorus pentoxide as the core substrate, compounded with anti-coking components, which can effectively regulate the acid-base properties of the catalyst surface, reduce the activity of olefin polymerization, reduce the formation of coking precursors, and simultaneously optimize the catalyst pore structure, improving material mass transfer efficiency.
[0052] The embodiments described above are merely preferred embodiments of the present invention, but the present invention is not limited to the specific details of the above embodiments. Within the scope of the technical concept of the present invention, several modifications and improvements can be made to the technical solution of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this patent should be determined by the appended claims.
Claims
1. A method for preparing a dual-phosphorus-source gradient stratified catalyst, characterized in that: Includes the following steps: Step 1: Carrier pretreatment: The alumina carrier is calcined and then set aside for later use; Step 2: Gradient construction of dual synergistic active layers: First, prepare a metal single-atom precursor solution, impregnate the support, and then age, dry, and calcine to form the first active layer; A mixed solution containing an active phosphorus source and a transition metal precursor was prepared, impregnated, and then calcined to generate transition metal phosphide clusters in situ, forming a second active layer, thus obtaining a carrier with a double active layer. Step 3: Constructing the inner transitional anti-carbon deposition layer: Prepare an impregnation solution containing phosphorus pentoxide and the first anti-carbon deposition additive, perform secondary modification on the carrier loaded with the double active layer, and obtain the third transitional anti-carbon deposition layer through impregnation, aging, drying and calcination. Step 4: Construct the outer anti-carbon deposition functional layer: Prepare a composite impregnation solution containing phosphorus pentoxide and a second anti-carbon deposition additive, and load the third transition anti-carbon deposition layer onto the outermost layer using a surface gradient impregnation method. After aging, drying, and final calcination, the final gradient-layered catalyst is obtained.
2. The method according to claim 1, characterized in that, The alumina support is γ-Al₂O₃ with a specific surface area of 180-280 m². 2 / g, pore volume 0.4-0.8 cm³ 3 / g, the carrier morphology is one of spherical, strip-shaped or toothed spherical; the sintering temperature is 400-500℃ and the sintering time is 2-4h.
3. The method according to claim 1, characterized in that, The active component in the first active layer is a metal single atom, and the metal precursor is one or more metal salt aqueous solutions selected from Ni(NO3)2, Mn(NO3)2, Zr(NO3)4, Fe(NO3)3, AgNO3, Pt(NO3)2, Pd(NO3)2, and Au(NO3)2, which are loaded by an equal volume impregnation method.
4. The method according to claim 1, characterized in that, The active component in the second active layer is a transition metal phosphide cluster, which is one or more of CoP, MoP, CuP2, Ni2P, WP, and VP.
5. The method according to claim 1, characterized in that, The active phosphorus source is one or two of phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate, and ammonium hypophosphite, with a loading of 0.1-2 wt% (calculated as P).
6. The preparation method according to claim 1, characterized in that, The third transitional anti-carbon deposition layer is composed of phosphorus pentoxide and an anti-carbon deposition additive, wherein the first anti-carbon deposition additive and the second anti-carbon deposition additive are one or more of silicon dioxide, titanium dioxide, and zinc oxide.
7. The preparation method according to claim 1, characterized in that, In step 2, the single-atom precursor is impregnated for 2-4 hours, aged for 1-2 hours, dried at 100-120℃ for 4-6 hours, and calcined at 400-480℃ for 2-3 hours; the impregnation, drying, and calcination processes of the transition metal phosphide precursor are consistent with those of the single-atom active layer. In steps 3 and 4, the impregnation time is 1-3 hours, the aging time is 0.5-1 hour, the drying temperature is 110-130℃, the drying time is 3-5 hours, the calcination temperature is 380-450℃, and the calcination time is 1.5-2.5 hours.
8. A dual-phosphorus source gradient stratified catalyst, prepared by the method according to any one of claims 1-7, characterized in that, Based on the total mass of the catalyst, the total loading of the metal dual synergistic active system is 1-8 wt%, the loading of the protective phosphorus source phosphorus pentoxide is 2-10 wt%, and the total loading of the anti-carbon deposition additive is 1-3 wt%.
9. The application of the dual phosphorus source gradient stratified catalyst according to claim 8 in the catalytic synthesis of ethanethiol.
10. The application according to claim 9, characterized in that, The catalyst is used in the catalytic reaction of ethylene sulfidation to prepare ethanethiol, under the conditions of 180-210℃, 1.1-1.6 MPa, an ethylene to hydrogen sulfide molar ratio of 1:1.05-1.2, and a volume hourly space velocity of 800-1200 h⁻¹. -1 Ethylene conversion rate ≥98%, ethanethiol selectivity ≥96%.
